Inhospital outcomes of implantation of a centrifugal left ventricular assist device in patients with endstage heart failure: experience of the Chazov National Medical Research Center of Cardiology - K. G. Ganaev; E. V. Dzybinskaya; O. Yu. Narusov; E. E. Vlasova; V. A. Amanatova; Zh. A. Shakhramanova; R. S. Latypov; K. V. Mershin; D. V. Pevzner; S. N. Tereshchenko; A. A. Shiryaev; R. S. Akchurin; et al. (Российский кардиологический журнал)
Aim. To study the inhospital outcomes of implantation of a centrifugal left ventricular assist device (LVAD) in patients with end-stage heart failure (HF).Material and methods. There were following inclusion criteria: estimated body surface area >1,2 m2, end-stage HF, LV ejection fraction <30%, cardiac index <2,2 l/min, long-term optimal therapy for HF. Patients were considered for implantation of a centrifugal (LVAD) as part of the final therapy, but subsequent heart transplantation was not ruled out if appropriate.Results. LVAD was implanted in 23 patients. All patients were men (mean age, 59,1±10 years; mean body mass index, 26±4,6 kg/m2). Ten patients had dilated cardiomyopathy, while 13 — ischemic one. Diabetes was revealed on in 3 (13%) patients, while chronic kidney disease and cancer — in 3 (13%) and 4 (17%) patients, respectively. The mean value of the six-minute walk test (6MWT) upon admission to the hospital was 257±71 meters. In one patient with gastric cancer, the device was implanted as a part of bridging therapy strategy. Thirty-day mortality was 9% (n=2). One of the deceased patients had a long history of end-stage heart failure, body weight deficiency, and frailty with severe muscle weakness. The second death was the result of early postoperative right ventricular failure. At discharge, patients had optimal LVAD performance based on anthropometric characteristics and physical activity. According to echocardiography, the criteria for unloading the left heart chambers have been achieved. The distance of 6MWT at discharge was 298±78 meters.Conclusion. Inhospital outcomes of implantation of a centrifugal LVAD in patients with end-stage HF demonstrate high efficiency in supporting systemic hemodynamics with an acceptable safety profile in patients with extremely high perioperative risk.